Prediabetes is associated with proteinuria development but not with glomerular filtration rate decline: A longitudinal observational study. Issue 8 (6th June 2021) - Furukawa, Mariko; Onoue, Takeshi; Kato, Kiminori; Wada, Takashi; Shinohara, Yukito; Kinoshita, Fumie; Goto, Motomitsu; Arima, Hiroshi; Tsushita, Kazuyo
Abstract: Aims: Diabetes is recognized as the leading cause of chronic kidney disease (CKD); however, the association of prediabetes with CKD remains unclear, in particular, the independent effect of prediabetes on proteinuria or estimated glomerular filtration rate (eGFR) has not been evaluated. This study aimed to investigate the associations of prediabetes with the proteinuria development and with eGFR decline separately in the Japanese general population without CKD. Methods: Participants who underwent health check‐ups in 2014 and had adequate data after 2 years were retrospectively analysed. A total of 405, 487 participants without CKD (eGFR, ≥60 ml min −1 1.73 m −2, with negative or trace urinary protein) at baseline were categorized according to fasting plasma glucose as having diabetes (≥126 mg/dl [7.0 mmol/l]), prediabetes (100–125 mg/dl [5.6–6.9 mmol/l]) or normal glucose level (˂100 mg/dl [5.6 mmol/l]). Logistic regression analysis was used to analyse the effects of prediabetes (vs. normal glucose level) on the proteinuria development (urinary protein of ≥1+) and eGFR decline (˂60 ml min −1 1.73 m −2 ) after 2 years. Results: After 2 years, 7037 participants (1.7%) developed proteinuria alone, 19, 015 (4.7%) presented eGFR decline alone and 636 (0.2%) showed both proteinuria and eGFR decline. Compared to normal glucose level and adjusting for prognostic factors, prediabetes was independently associated with the proteinuria development (odds ratio [OR] 1.233; 95% confidence interval [CI] 1.170–1.301], whereas prediabetes was not associated with eGFR decline (OR 0.981; 95% CI 0.947–1.017). Conclusions: Prediabetes is associated with the proteinuria development but not with eGFR decline in the general population.